A Team of Five Million? : The 2020 'Covid-19' New Zealand General Election. - Curtin, Jennifer.; Greaves, Lara.; Vowles, Jack (ANU Press, 2024)
New Zealand was one of a handful of countries that held a national election in the midst of the Covid-19 pandemic.
Keywords: Elections -- New Zealand; New Zealand -- Politics and government -- 1972-; New Zealand Parliament -- Elections, 2020; Political campaigns

Te Tiriti o Waitangi relationships: people, politics and law - Turei, Metiria; Wheen, Nicola R.; Hayward, Janine (Bridget Williams Books, 2024)
"The third in a series committed to discussions of Te Tiriti o Waitangi/Treaty of Waitangi issues. These essays from... scholars and researchers take a dynamic approach to understanding Tiriti/Treaty relationships, acknowledging the ever-evolving interplay between the Crown and Māori through time. The book addresses pressing issues like Treaty principles, sovereignty, the UN Declaration on the Rights of Indigenous Peoples, and manawhenua relationships to Te Tiriti and settlements. It emphasises the roles of tikanga and rangatiratanga in fostering genuine progress, and envisions a future guided by these principles in advancing Māori–Crown relationships"--Publisher's website.
Keywords: Kāwanatanga.; Mana whakahaere.; Māori (New Zealand people) -- Civil rights.; Māori (New Zealand people) -- Government relations.; Māori (New Zealand people) -- Legal status, laws, etc.; Noho a-iwi.; Tiriti o Waitangi.; Treaty of Waitangi